Protective effect of fluorides on erosion and erosion/abrasion in enamel: a systematic review and meta-analysis of randomized in situ trials - Zanatta, Rayssa Ferreira [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Scaramucci, Tais; El Dib, Regina [UNESP]; Maia, Lucianne Cople; Ferreira, Daniele Masterson Tavares Pereira; Borges, Alessandra Bühler [UNESP] (Elsevier, 2020)
Objectives: To evaluate the effects of different fluoride types and vehicles when compared to water or placebo, on prevention of enamel erosion and erosive tooth wear progression. Design: A systematic review followed by meta-analysis of randomized in situ trials was conducted. PubMeb, Scopus, Web of Science, LILACS, BBO, Scielo, EMBASE and CENTRAL electronic databases were searched. Studies with fluoride compounds (NaF, AmF, Sn, TiF4) and vehicles (toothpaste, mouth rinse, gel, and varnishes) compared to control (water or placebo) for control of enamel loss progression were included. Reviewers independently screened potentially eligible articles, extracted data, and assessed risk of bias. GRADE approach was used to rate the overall certainty of evidence for toothpastes and rinses under erosive/abrasive challenges. Results: Thirty-two studies were elegible. Under erosive/abrasive challenges, enamel loss was significantly lower than control for NaF toothpastes [Mean difference(MD) -1.14; Confidence Interval(CI) -1.89 to -0.40] and Sn/associations [-6.02; -11.09 to -0.95], while no difference was found for AmF [-13.59; -39.7 to -12.52]. For mouth rinses, Sn/associations solutions were effective [-11.49; -16.62 to -6.37], but NaF showed no significant effect [-2.83; -8.04 to 2.38]. Conclusion: Overall, fluoride products are able to reduce enamel loss when compared to control, but results must be interpreted with caution. For toothpastes, NaF provided limited protection, with moderate evidence, while Sn/associations exhibited protective effect with low certainty of evidence. For rinses, NaF was not effective, with very low evidence, while the stannnous enriched fluorides offered higher protection regarding enamel erosion and erosive wear, with moderate certainty of evidence.
Keywords: enamel; erosion; fluorides; randomized in situ clinical trials; systematic review; tooth wear